Synaptic and neural pathway redundancy enables the robustness of a sensory-motor reflex and promotes predation escape in Caenorhabditis elegans - HaoMing He; Eugenia King Hin Fong; Sandeep Kumar; Ho Ming Terence Lee; Andrew M. Leifer; Martin Chalfie; Chaogu Zheng (Proceedings of the National Academy of Sciences, 2026)
As a basic unit of the nervous system, the sensory-motor reflex circuit is fast and robust. However, it is not entirely clear how this robustness is achieved, given that various genetic perturbations can alter the function of the sensory neurons. By mapping the molecular basis of neuronal connections in the touch response circuit of Caenorhabditis elegans , we found prevalent genetic redundancy at neural pathway, synaptic, and molecular levels, which ensures that sensory signals can be relayed to command interneurons that control motor output. We also found developmental remodeling of the anterior circuit, which leads to the pruning of larval synapses, establishment of a second pathway that activates additional interneurons, and lateralization of the circuit. Finally, we found that the synapses that appeared to be functionally redundant in a simple touch assay contribute to the extent of reversal response in an additive manner, which may help the organism escape from predators.